2013
DOI: 10.1080/17588928.2011.634064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three levels of arousal on 3-back working memory task performance

Abstract: This study investigated how three levels of arousal affected performance of a 3-back working memory task. Ten female and ten male university students participated in this experiment. With pictures selected from a group test, three levels of arousal were induced--i.e., tense, neutral, and relaxed emotions. Each subject was run through the procedure three times, once for each arousal level. The procedure consisted of six phases for each arousal condition: (1) Rest 1 (2 min), (2) Picture 1 (presenting emotion aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 19 publications
1
26
1
Order By: Relevance
“…This finding is inconsistent with previous results that showed that a comfortable learning environment had a positive impact on students' task performance [17]. The answer given was that the arousal level of each participant was higher than the arousal level for optimal performance [4].…”
Section: Introductioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This finding is inconsistent with previous results that showed that a comfortable learning environment had a positive impact on students' task performance [17]. The answer given was that the arousal level of each participant was higher than the arousal level for optimal performance [4].…”
Section: Introductioncontrasting
confidence: 57%
“…Furthermore, stress behaviours affecting learning as perceived by the two groups of students did not differ significantly. In addition, no correlation existed between the perceived indoor thermal discomfort levels and stress behaviour levels affecting learning for students in LTH-2, because the arousal level of the students in the thermal environment was likely higher than the arousal level for optimal performance [3,4]. However, a correlation existed in the case of students in LTH-3, which was expected because it only confirmed the widely-accepted view that stress behaviours exhibited by students in any learning can have a profound effect on learning.…”
Section: Introductionmentioning
confidence: 99%
“…One answer could be that the arousal level of each participant was higher than the arousal level for optimal performance [21]. According to the two-dimensional model of emotion, valence, i.e., comfort and discomfort, forms one axis, with arousal as another axis perpendicular to it.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Considering that PTS can be calculated as an absolute value in the difference between actual indoor temperature and participants' perceived temperature, participants were asked to estimate the current room temperature. Furthermore, based on the findings of Choi et al (2013) that the arousal level of individuals also affects performance, this study assessed the arousal level of participants by using a Likert scale, with 1 indicating "relaxed" and 5 indicating "aroused." [21] 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation